Pengaruh Sosial Media Influencer Terhadap Perilaku Konsumen Dalam Memilih Produk Fashion Di Toko Putri Agata - Juwani; Sugeng Widakdo; Ovriyadin (Hikamatzu | Journal of Multidisciplinary, 2025)
The purpose of this study is to determine whether Social Media Influencers have a significant influence on consumer behavior in choosing fashion products at Putri Agata Store. The type of research is associative, the research instrument uses a questionnaire with a Likert scale. The population used is all consumers who have shopped at Putri Agata Store whose number is unknown, the number of samples in this study was 80 respondents with a sampling technique that is purposive sampling. Data collection techniques with observation, questionnaires, and literature studies. Data analysis techniques by conducting validity tests, reliability tests, simple linear regression tests, correlation coefficients, determination tests, and t tests. The results of this study indicate that there is an influence between Social Media Influencers on Consumer Behavior in choosing fashion products at Putri Agata Store